Ambient assisted living platform for remote monitoring of bedridden people - Pereira, F. (2015)
The aim of this paper is to present a platform for remote monitoring of bedridden people developed in the context of Ambient Assisted Living (AAL). This platform, Medical Care Terminal (MCT), includes the measurement of biomedical data (body temperature, galvanic skin resistance, electrocardiogram and electromyogram, level of oxygen, body position and breathing) as well environmental data (level of alcohol in the air, carbon monoxide level in the air, brightness and temperature). It presents three main issues, namely: it has a user-friendly interface; it is simple to use by a single elderly person; it can be adapted to the needs of a specific patient (custom-made solution), as the system can be configured in function of the measurements required for that specific patient (modular configuration). Finally, it is a low cost solution, affordable for low budget markets.